The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1089/ped.2010.0022
|View full text |Cite
|
Sign up to set email alerts
|

Home is Where the Triggers Are: Increasing Asthma Control by Improving the Home Environment

Abstract: Asthma remains the most common chronic condition of childhood. Strong evidence has linked exposure to allergens and other triggers commonly found in homes to allergen sensitization and asthma incidence and morbidity. A growing body of evidence has demonstrated that a home visit strategy that includes an environmental component that addresses multiple triggers through multiple interventions is effective. Such home visits reduce exposure to triggers, decrease symptoms and urgent health-care use, and increase qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 68 publications
1
46
0
2
Order By: Relevance
“…Previous studies have shown that indoor and outdoor environmental pollution are major factors contributing to higher risk for asthma attacks and higher cost of asthma. People with lower incomes often live in places with higher concentrations of environmental asthma triggers (49)(50)(51)(52). On one hand, the results of this study suggest that poor people (with incomes ,100% of the poverty threshold) have significantly higher medical costs because of asthma than those with higher incomes.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that indoor and outdoor environmental pollution are major factors contributing to higher risk for asthma attacks and higher cost of asthma. People with lower incomes often live in places with higher concentrations of environmental asthma triggers (49)(50)(51)(52). On one hand, the results of this study suggest that poor people (with incomes ,100% of the poverty threshold) have significantly higher medical costs because of asthma than those with higher incomes.…”
Section: Discussionmentioning
confidence: 69%
“…This was an independent association between sharing a bedroom and the level of asthma control, after controlling for household income and number of siblings, along with other covariates (Table 2). Sharing a bedroom is a measure of crowding [40], which has been reported to decrease asthma control [41]. The seemingly contradictory effects of increased number of siblings and sharing a bedroom can be partially explained by our data, which showed that in the low income group (less than SAR 15 000), there was a strong positive relationship between the number of siblings (0-1 versus 2-3 versus 4 and more) and the prevalence of sharing a bedroom (34.8% versus 84.4% versus 95%, p50.001), whereas in the high-income group (SAR 15 000 or more) there was only a marginally significant association (20.0% versus 35.1% versus 52.2%, p ¼ 0.066).…”
Section: Discussionmentioning
confidence: 99%
“…According to Krieger (2010), multitrigger, multicomponent interventions are more effective than single-component interventions. Davis, Gordon, and Burns (2011) proclaimed further that interventions for children with asthma must be comprehensive, and include not only caregivers and school staff, but also focus on symptom management and avoidance, or a reduction of environmental triggers.…”
Section: Impact Of Environmental Interventions On Asthma Outcomesmentioning
confidence: 99%